1996
DOI: 10.1002/(sici)1096-9861(19960729)371:3<448::aid-cne7>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mitochondrial protein synthesis inhibition on deafferentation?induced ultrastructural changes in nucleus magnocellularis of developing chicks

Abstract: Following cochlea removal in developing chicks, about 30% of the neurons in the ipsilateral second-order auditory nucleus, nucleus magnocellularis, undergo cell death. Administration of chloramphenicol, a mitochondrial protein synthesis inhibitor, results in a pronounced increase in deafferentation-induced cell death. In this study, we examined whether the chloramphenicol enhancement of deafferentation-induced cell death reveals the same ultrastructural characteristics that are seen in degenerating nucleus mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…I n nucleus magnocellularis auditory neurons, mitochondria are clearly involved in the cellular response to deafferentation. Previous studies revealed significant morphological changes in neuronal mitochondria, including rapid proliferation across the entire deafferented nucleus (Hyde and Durham, 1994), ultrastructural vacuolization within the subset undergoing ribosomal degradation and endoplasmic reticulum (ER) fragmentation (Born and Rubel, 1985;Rubel et al, 1991;Hyde and Durham, 1994;Hartlage-Rubsamen and Rubel, 1996), and loss of mitochondrial DNA integrity in the subset destined to die (Karnes et al, 2009). Here, we demonstrate disturbances in mitochondrial functional status in deafferented neurons as a corollary to the previously described alterations of mitochondrial structure.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…I n nucleus magnocellularis auditory neurons, mitochondria are clearly involved in the cellular response to deafferentation. Previous studies revealed significant morphological changes in neuronal mitochondria, including rapid proliferation across the entire deafferented nucleus (Hyde and Durham, 1994), ultrastructural vacuolization within the subset undergoing ribosomal degradation and endoplasmic reticulum (ER) fragmentation (Born and Rubel, 1985;Rubel et al, 1991;Hyde and Durham, 1994;Hartlage-Rubsamen and Rubel, 1996), and loss of mitochondrial DNA integrity in the subset destined to die (Karnes et al, 2009). Here, we demonstrate disturbances in mitochondrial functional status in deafferented neurons as a corollary to the previously described alterations of mitochondrial structure.…”
Section: Discussionsupporting
confidence: 75%
“…Calcium influx triggers rapid proliferation of mitochondria within NM neurons (Hyde and Durham, 1994). Mitochondria unable to buffer the rise in calcium undergo vacuolization (Hyde and Durham, 1994;Hartlage-Rubsamen and Rubel, 1996), whether in response to persistent elevated calcium levels (Brookes et al, 2004) or from the loss of ER-mitochondrial junctional integrity (Pinton et al, 2008). ER-mitochondrial junctional impairment releases lipids and calcium into the cellular cytoplasm, which perpetuates ROS generation (Nicholas and Hyson, 2006;Nicholls, 2008), shifts metabolism toward the TCA cycle (Duchen, 2004;Gunter et al, 2004), and increases SDH levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…71 When investigated further, it was found that inhibition of mitochondrial but not cytoplasmic protein synthesis specifically potentiates cell death in NM after afferent deprivation. 69,70,74 These observations indicate a protective role for mitochondria in determining cell fate after deafferentation.…”
Section: The Auditory System As a Model For Apoptotic Cell Death: Mitmentioning
confidence: 80%
“…64,67,68 During this process, these neurons undergo characteristic metabolic and morphologic changes similar to apoptosis. 69,70 These changes include (but are not limited to) an increase in mitochondrial density, an increase in in-tracellular calcium, decreased RNA and protein synthesis, and changes in oxidative metabolism. 67,[71][72][73] Once again, it appears that mitochondria are of central importance in determining cell survival in this model.…”
Section: The Auditory System As a Model For Apoptotic Cell Death: Mitmentioning
confidence: 99%